Comparison of Early Postoperative Diaphragm Muscle Function after Lobectomy via VATS and Open Thoracotomy: A Sonographic Study - Kocjan, Janusz; Rydel, Mateusz; Czyżewski, Damian; Adamek, Mariusz (Life (Basel, Switzerland), 2024)
Although a growing body of evidence emphasizes the superiority of VATS over conventional thoracotomy, little is still known about early postoperative diaphragm muscle function after lobectomy via these two approaches. To fill the gap in existing literature, we conducted a comparative study between VATS and conventional thoracotomy in terms of postoperative diaphragm muscle function, assessing its contractility, strength, the magnitude of effort and potential risk of dysfunction such as atrophy and paralysis. A total of 59 patients (30 after VATS), who underwent anatomical pulmonary resection at our institution, were enrolled in this study. The control group consisted of 28 health subjects without medical conditions that could contribute to diaphragm dysfunction. Diaphragm muscle was assessed before and after surgery using ultrasonography. We found that both surgical approaches were associated with postoperative impairment of diaphragm muscle function—compared to baseline data. Postoperative reduction in diaphragm contraction was demonstrated in most of the 59 patients. In the case of the control group, the differences between measurements were not observed. We noted that lobectomy via thoracotomy was linked with a greater percentage of patients with diaphragm paralysis and/or atrophy than VATS. Similar findings were observed in referring to diaphragm magnitude effort, as well as diaphragm contraction strength, where minimally invasive surgery was associated with better diaphragm function parameters—in comparison to thoracotomy. Disturbance of diaphragm work was reported both at the operated and non-operated side. Upper-right and left lobectomy were connected with greater diaphragm function impairment than other segments. In conclusion, the VATS technique seems to be less invasive than conventional thoracotomy providing a better postoperative function of the main respiratory muscle.